Sistem Ecobrick Perancangan Sistem Ecobrick Untuk Mengatasi Masalah Sampah Plastik Demi Menunjang Desa Wisata di Pulau Mubut Darat - Dodi Prima Resda; Muhammad Zainuddin Lubis; Muhammad Ghazali (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
Abstract— Service activities are very important, especially in love for the environment, especially in coastal and ocean areas, in the Riau Archipelago, Indonesia. Garbage is a very important topic to discuss, and solutions are always sought to overcome waste problems, especially in prospective tourist sites, namely Pulau Mubut Darat, Riau Islands. This service activity provides the design and manufacture of ecobricks by utilizing plastic waste, which can overcome domestic waste processing problems, especially from coastal communities in prospective tourist sites on the islands, namely in Mubut Darat. The methods in this service activity are preparing tools and materials, surveying waste locations, extension workers and making waste using the ecobrick method, as well as evaluation and monitoring. The results of this service are Generating steps for making ecobricks, knowing the location of household plastic waste collection locations, counseling and making ecobricks using plastic waste. This service is expected to be sustainable in the future in order to create an independent tourist village and provide income for coastal communities on Mubut Darat Island, Riau Islands.